Long-term gabapentin treatment impairs cognitive function in aged mice via tau hyperphosphorylation - Xia, Suyun; You, Zerong; Wu, Xinbo; Yang, Jinsheng; Wang, Shiyu; Li, Na; Dai, Jiajia; Dong, Yuanlin; Chen, Lucy; Yan, Min; Shen, Shiqian; Xie, Zhongcong; et al. (Frontiers in Pharmacology, 2025)
IntroductionGabapentin (GBP) is widely prescribed to older patients for pain management. Recent clinical studies highlight that GBP adversely affect cognitive function in older patients. GBP binds to the α2δ1 subunit of L-type voltage-gated Ca2+ channels to inhibit Ca2+ channel current. It is being increasingly recognized that GBP affects neuronal activity in multifaceted ways. However, the molecular mechanism underlying GBP’s impact on cognitive function in older subjects remains unelucidated.MethodsAged mice (18-month-old, female) were subjected to spared nerve injury (SNI) or sham surgery and treated with GBP for 60 days. Learning and memory were assessed using novel object recognition (NOR) test and contextual and cued fear conditioning test (FCT). Adeno-associated viral vector (AAV) was used for gene overexpression in the brain. Brain tissue was analyzed by Western blot, qRT-PCR, and protein activity assay.ResultsLong-term GBP treatment impaired learning and memory in aged mice with or without nerve injury-induced pain as GBP-treated aged mice had lower novel object recognition index in NOR test and shorter freezing time in FCT, respectively. In the hippocampus of GBP-treated mice, increased levels of p-tau (S416) and p-tau (S262) were observed, together with increased CaMKIIα and decreased Sirt1 expression. AAV-mediated Sirt1 overexpression in the hippocampus or systemic administration of the Sirt1 activator resveratrol prevented cognitive impairment and tau hyperphosphorylation via enhancing Sirt1 activity in GBP-treated mice.ConclusionLong-term GBP treatment is detrimental to cognitive function in aged mice. GBP suppressed Sirt1 expression, leading to elevated CaMKIIα level and hyperphosphorylation of tau, and boosting Sirt1 activity curbed the adverse effect of GBP on memory in aged mice.